ANALYSIS OF RAW MATERIAL COST VARIANCES AS AN INSTRUMENT FOR MANAGEMENT CONTROL AND A DETERMINANT OF FINANCIAL INFORMATION QUALITY - Ardiansyah Ardiansyah; Kalsum Lussy; Barus Umarella; Abdulharis Tamalene (Jurnal Cinta Nusantara, 2026)
Background: This study aims to identify deviations between actual food cost and standard food cost within the integration of cost accounting and financial accounting, as well as to evaluate their implications for financial reporting quality. Method: This study employed a mixed-methods approach with an explanatory design. Quantitative descriptive analysis was conducted using revenue reports and records of food and packaging material usage over a 30-month period through cost variance analysis. Qualitative data were collected through interviews with internal company personnel regarding raw material control practices. Findings: The results indicate that actual food costs consistently exceeded standard costs, reflecting inefficiencies in raw material management. Cost variances contributed to higher cost of goods sold and lower earnings information quality. Qualitative findings reveal that the main causes of variance include suboptimal supplier selection, fluctuations in raw material quality, inappropriate storage methods, and weak inventory control. Conclusion: The study confirms that effective raw material control is essential for improving operational efficiency and the reliability of financial information. Novelty/Originality: This study highlights that cost variance functions not only as a cost control instrument in cost accounting but also as a determinant of information quality in financial accounting.